RETARDED GROWTH OF LOWLAND RICE IN SALINE SOIL INOCULATED WITH NITROGEN-FIXER AZOTOBACTER - Reginawanti Hindersah; Alia Halimatusy; Benny Joy; Mieke Rochimi Setiawati; Diyan Herdiyantoro (Jurnal Agroekoteknologi, 2020)
Low-land rice (Oryza sativa L.) cultivation in saline soils face some constraints include nitrogen availability. Saline-resistant nitrogen fixing bacteria Azotobacter are expected to increase supply nitrogen in saline soils. The objectives of the study were to determine the effect of liquid inoculant concentration of two Azotobacter isolates on early vegetative growth of lowland rice grown in potted saline soil.  The greenhouse trial design was a randomized block design with seven treatments and four replications. The treatments were combination of isolates and Azotobacter liquid inoculant concentrations in single and mixed inoculation. The results showed that all plants experienced chlorosis and stunt due to high Electrical Conductivity. Inoculation of different isolates and concentrations did not influence the growth of lowland rice in soil with high EC at the end of experiment. Therefore, neither isolates nor concentration of Azotobacter could improve retarded-growth of lowland rice in saline soil.